PENGARUH PENAMBAHAN LILIN LEBAH DAN NANOPARTIKEL SENG OKSIDA TERHADAP SIFAT FISIK DAN MEKANIS FILM BERBASIS KITOSAN - Novan Nandiwilastio; Tien R. Muchtadi; Nugraha E. Suyatma; Sri Yuliani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Chitosan-based films showed good gel formation capability and gas permeability (CO2 and O2). However, the high permeability of water vapor limits the application of chitosan as a single coating material. Additionally, single chitosan film was also brittle, so the addition of lipid and metal nanoparticles were chosen to solve this problem. This research aimed to determine the effect of the addition of beeswax emulsion and zinc oxide nanoparticles (ZnO-NPs) on the physical and mechanical properties of chitosan based films. The film was prepared by dissolving ZnO-NPs (0, 1 and 2% by weight of chitosan) into 100 mL of distilled water followed by the addition 1 g of chitosan and or, addition of beeswax emulsion (0 and 5% by the volume of solution). The result showed that the addition of beeswax emulsion ZnO-NPs into chitosan based film significantly decreased WVTR value from 24.03 to 10.38 g/m2 hours and the tensile strength value from 8.30 to 6.92 Mpa. The addition of beeswax emulsion and ZnO-NPs also changed the physical properties of chitosan-based film significantly; in terms appearance, color and thickness. Mean-while, the film elongation percentage changed significantly in the range of 30.36 to 50.09 % when ZnO-NPs was added into chitosan-based film solution. Overall, the addition of beeswax and ZnO-NPs showed improvement of the physical and mechanical properties of chitosan-based films so that better packaging of fresh food products can be developed.